Profil Aktivitas Farmakologis Daun Pepaya Segar pada Sistem Saraf: Suatu Kajian Berdasarkan Perbedaan Konsentrasi - Nurul Izzatul Jannah; Husnul Hatima; Dhiva Rabiatul Maulia; Nurazizah Khairani; Fauziah Zakilah; Rahasia Rahasia; Sisma Efendi; Nur Aulia; Muh.Yusuf Al Habib Rachman; Andi Utari Prasetya Ningrum (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The extract of Carica papaya L. leaves contains phytochemical compounds such as flavonoids, alkaloids, phenolics, and saponins that play a role in biological activities, including antioxidants, anti-inflammatory, analgesic, and modulation of the nervous system. This study aims to evaluate the effects of fresh papaya leaf extract on the central nervous system (CNS) and autonomic nervous system based on varying extract concentrations. The study used test animals with treatment groups consisting of negative control, positive control, and extracts at concentrations of 4%, 8%, and 16%. Parameters observed included parasympathomimetic (PSM), parasympatholytic (PSL), sympathomimetic (SM), sympatholytic (SL), analeptic effects (ANA), CNS stimulation (SSSP), CNS depression (DSSP), and muscle relaxation (RO). The results showed that the 16% concentration produced the highest PSM activity (46.82%) and dominant CNS stimulation (38.59%), while DSSP and RO decreased at higher concentrations. This phenomenon indicates that increasing the extract concentration does not always enhance CNS depression, but rather leads to stimulation. These findings support the potential of papaya leaf extract as a neuroprotective and multifunctional agent. Further research is needed to confirm its molecular mechanisms and clinical effectiveness as a phytotherapy candidate.